Feasibility Study Of Vacuum Technology Integrated Fused Deposition Modeling To Reduce Staircase Effect - Saiful Bahri, Mohamed; S., Maidin; A.S., Mohamed; S., Akmal (2018)
Fused deposition modeling (FDM) is currently one of the most used AM technologies and has been around in various industries since its tremendous offering. Most semi-molten layered thermoplastic surface often uneven, which lead to rough and poor surface finish. The FDM process involves temperature gradient since the material extrude was in a semi-molten state. The thermal stresses present and affect the surface quality. This paper proposes an idea of using vacuum technology to reduce the “staircase effect” parts printed. The FDM machine remains in a rectangular acrylic chamber, an oil-flooded-vacuum pump connected will absorb the air inside the chamber until desire pressure while printing object. Mitutoyo SJ-301 portable surface roughness tester and optical microscope used to analyze the quality of surface finish. Result reveal with vacuum technology, improve 9% from normal print.